Assessment of sustainability of logistic activity of Port of Klaipeda - Kutkaitis, Audrius; Šimanskienė, Ligita; Burgis, Darius (Univerzita Pardubice, 2014)
In this article we analyze the relation between sustainable development and logistic activity of sea ports. The assessment of sustainability of development of logistic activity in seaports is important for determining current trends of development, to indicate problematic areas and to develop means of adjusting development according to predetermined goals. The main problem that the article deals with is the complexity of sustainable development assessment that usually requires specific approach when trying to determine sustainability of specific activity of specific organization. In this article we showed how we used a developed instrument to assess sustainable development of logistic activity of Port of Klaipeda. We determined that social level of sustainable development, developed especially fast in Port of Klaipeda, but it was not related to the development of the ecological and economic levels, general trends of sustainable development tended to decrease.
Keywords: sustainable development; logistics; seaports; assessment; transportation